An unusual promotion of γ-crystals in metallocene-made isotactic polypropylene from orientational relaxation and favorable temperature window induced by shear. (3rd January 2018) - Wang, Yan; Zhao, Jian; Qu, Minjie; Guo, Jing; Yang, Shu-Gui; Lei, Jun; Xu, Jia-Zhuang; Chen, Yan-Hui; Li, Zhong-Ming; Hsiao, Benjamin S.
Abstract: Combined effects of shear flow and non-isothermal processing, which were akin to the practical industrial processing, on the crystallization of metallocene-made isotactic polypropylene (m- i PP) were investigated by in-situ synchrotron wide-angle X-ray diffraction (WAXD) and small-angle X-ray scattering (SAXS) techniques. The simultaneous appearance of α - and γ -crystals was observed in quiescent samples, while shear flow led to the occurrence of α -crystals prior to γ -crystals at the initial stage of crystallization. Although the local alignment of chain segments promoted by shear flow facilitated the α -crystals, the relaxation of oriented chains was experimentally confirmed to boost the formation of γ -crystals. Interestingly, the resultant γ -crystal content was higher in the sheared samples than the quiescent counterparts at a given cooling rate and further increased with the decrease of cooling rates. Such a discrepancy was not only related to shear-induced orientation and relaxation, but also was accredited to the advanced crystallization temperature window, which was favorable for the γ -crystal growth. It was quite different from the isothermal crystallization situation, where the formation of γ -crystals was depressed in presence of shear flow. The dynamic competition between α -crystal and γ -crystal formation under the effects of shear during the non-isothermal crystallization was discussed. Our work is of valuable reference to tailor the crystalline structure of m- i PP during practical processing and hence to acquire the desired performance of products. Graphical abstract: Image 1 Highlights: The relaxation of oriented chains plays a critical role in γ-crystal formation. The promoting effect of γ-crystals at final stage of crystallization in sheared samples is analytically addressed. Evolution mechanism of γ-crystal formation under shear flow and non-isothermal crystallization is proposed.